Enriched Pea Protein Texturing: Physicochemical Characteristics and Application as a Substitute for Meat in Hamburgers - Irene Peñaranda; María Dolores Garrido; Purificación García-Segovia; Javier Martínez-Monzó; Marta Igual (Foods, 2023)
There is currently a growing trend towards the consumption of vegetable protein, even if it shows some deficiencies in essential amino acids. It has been driven by consumer passion for health and wellness, environmental sustainability, animal welfare and the flexitarian lifestyle. However, the formulation of plant protein food analogues to meat products is complicated by the technological properties of isolated plant protein. One of the processes used to improve these properties is the texturisation of the protein by extrusion, as well as the use of other plant materials that can enrich the formulation. Therefore, the aim of this study was to evaluate the effect of pea protein (PP) enriched with lucerne (L), spinach (S) and Chlorella (C) in powdered and texturised forms on the physicochemical properties and extrusion parameters, and to evaluate its technological and sensory quality as a meat analogue in vegetal hamburgers. Texturisation reduced the number of soluble components released, thus reducing the molecular degradation in extruded material. The texturised samples were significantly (p < 0.05) less hygroscopic than the non-textured samples. Once the properties of the powder and texturised had been analysed, they were used to prepare vegetal hamburgers. The addition of vegetable-enriched texturised samples with high chlorophyll content led to more intense colour changes in the vegetal hamburgers during cooking, with PP+C providing the darkest colouring, and also resulted in a final product more similar to a traditional meat hamburger, with higher overall and meat odour/flavour intensity, hardness, juiciness and chewiness, and less legume and spice odour and flavour. Overall, texturisation improved the technological properties of the enriched protein isolate, allowing for more efficient production of vegetal hamburgers.